2006
DOI: 10.1590/s0100-40422006000600013
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos estruturais relacionados ao processo de troca iônica no niobato lamelar K4Nb6O17

Abstract: Recebido em 13/9/05; aceito em 21/3/06; publicado na web em 25/7/06 STRUCTURAL ASPECTS RELATED TO THE ION EXCHANGE PROCESS IN LAYERED NIOBATE K 4 Nb 6 O 17. The niobate with formula K 4 Nb 6 O 17 has a layered structure formed by stacked negative sheets and exchangeable cations in the interlayer region. In this study we discuss some structural aspects related to the ion exchange in layered hexaniobate based on X-ray diffractometry and vibrational Raman spectroscopy data. Hexaniobate has two distinct interlayer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
5
0
2
Order By: Relevance
“…2 shows that Raman spectra between both hexaniobates I and II exhibit significant modifications in the following regions: 950-800 cm -1 (Nb-O terminal stretching mode of highly distorted NbO 6 octahedra), 700-500 cm -1 (Nb-O stretching of slightly distorted octahedra) and 300-200 cm -1 (bending modes of the Nb-O-Nb linkages). The band at 900 cm -1 assigned to short Nb-O bonds shifts to 940 cm -1 after the replacement of K + by H + ions, as it was observed in other works [13,18]. This band also shows a shift for the high wavenumber region when the layered niobate oxides of composition KNb 3 O 8 and KCaNb 3 O 10 are protonated [12,13].…”
Section: Resultssupporting
confidence: 77%
“…2 shows that Raman spectra between both hexaniobates I and II exhibit significant modifications in the following regions: 950-800 cm -1 (Nb-O terminal stretching mode of highly distorted NbO 6 octahedra), 700-500 cm -1 (Nb-O stretching of slightly distorted octahedra) and 300-200 cm -1 (bending modes of the Nb-O-Nb linkages). The band at 900 cm -1 assigned to short Nb-O bonds shifts to 940 cm -1 after the replacement of K + by H + ions, as it was observed in other works [13,18]. This band also shows a shift for the high wavenumber region when the layered niobate oxides of composition KNb 3 O 8 and KCaNb 3 O 10 are protonated [12,13].…”
Section: Resultssupporting
confidence: 77%
“…[22][23][24] The acidic form of hexaniobate, H 2 K 2 Nb 6 O 17 , can be easily prepared by a cation-exchange reaction. 24,25 Moreover, it has been reported that protonic niobates and titanoniobates are promising materials to produce solid acid catalysts for different chemical reactions due to their high acidic surfaces. 26,27 Therefore, regarding the application of hexaniobate for designing hybrid materials with PANI, the H 2 K 2 Nb 6 O 17 form is very interesting because it could also act as a doping agent for the polymeric chains.…”
Section: Introductionmentioning
confidence: 99%
“…Liu [4,9] However, to the authors' knowledge no Raman and IR data have been published for K 4 Nb 6 O 17 and K 4 Nb 6 O 17 · 3H 2 O single crystals, and no detailed assignment of the observed bands has been proposed. Here we report the growth of large single crystals of both anhydrous and hydrated potassium hexaniobate as well as polarised Raman and IR studies of these crystals in order to get insight into origin of the observed phonon modes and influence of water intercalation on the phonon properties of this material.…”
Section: Introductionmentioning
confidence: 99%